Subacute toxicity of Elaeagnus angustifolia fruit seeds in rats - Gh Karimi; A Khoie; H Hosseinzadeh; SH Shojaie (Institue of Medicinal Plants, ACECR, 2003)
The subacute toxicity of Elaeagnus angustifolia fruit seeds extract was studied in rats. Seperate groups of animals were given intraperitoneal doses of extract at 0.125, 0.25 and 0.5 g/kg daily for two weeks. Blood samples and selected organs were prepared for biochemical, hematological and histological experiments. Significant reduction of RBC, HCT and Hgb were recorded in all doses. Doses of 0.25 and 0.5 g/kg increased ALT, AST, ALP and LDH significantly and induced sever injury to liver and heart, but low effect on kidney. The results indicated that the extract was toxic for liver , heart and kidney and caused normochrome normocyte anemia.